Cognitive Structures of the Concept of the “Perfect Man” in Khoja Ahmed Yasawi’s Hikmets (Eurasian Journal of Philology Science and Education, 2026)
The article offers a comprehensive analysis of the artistic and philosophical content of the concept of the “Perfect Man” in Khoja Ahmed Yasawi’s Hikmets. It argues that this concept originates in the works of Muslim thinkers such as Ibn Arabi, occupies a special place in Sufi doctrine, and has remained a significant theme in the spiritual space of Kazakh culture, particularly in the period preceding Abai. The concept of the “Perfect Man” in Yasawi’s Hikmets is examined as a form of spiritual and cognitive continuity rooted in the Sufi tradition and extended into its manifestations in modern literature. The study draws on R. Syzdykova’s work The Language of Yasawi’s Hikmets and the Tashkent manuscript version in order to identify the linguistic, worldview-related, and conceptual features of the text.The article compares the image of a person who has lost his true human essence with that of an individual who has attained spiritual perfection, revealing their significance and role in social life. Drawing on the views of various scholars, it analyzes the role of the Perfect Man as a figure who guides society along the path of truth, establishes justice and righteousness, condemns immoral habits, and promotes order and virtue. In addition, the study demonstrates the historical formation of the notion of perfection in Sufi teaching, its connection with the Turkic worldview, and its continuity within Kazakh spiritual culture.The results of the study may be used in teaching semantics-related disciplines in higher education, as well as in scholarly research devoted to Yasawi’s heritage, Sufi thought, and the concept of the Perfect Man.Key words: Yasawi, Hikmets, “Perfect Man”, concept, cognitive structure.